Loss of IRF2BP2 in Microglia Increases Inflammation and Functional Deficits after Focal Ischemic Brain Injury - Cruz, Shelly A.; Hari, Aswin; Qin, Zhaohong; Couture, Pascal; Huang, Hua; Lagace, Diane C.; Stewart, Alexandre F. R.; Chen, Hsiao-Huei (Frontiers in Cellular Neuroscience, 2017)
Ischemic stroke causes neuronal cell death and triggers a cascade of inflammatory signals that contribute to secondary brain damage. Microglia, the brain-resident macrophages that remove dead neurons, play a critical role in the brain’s response to ischemic injury. Our previous studies showed that IRF2BP2 regulates peripheral macrophage polarization, limits their inflammatory response and reduces susceptibility to atherosclerosis. Here, we show that loss of IRF2BP2 in microglia leads to increased inflammatory cytokine expression in response to lipopolysaccharide challenge and impaired activation of anti-inflammatory markers in response to interleukin-4 (IL4) stimulation. Focal ischemic brain injury of the sensorimotor cortex induced by photothrombosis caused more severe functional deficits in mice with IRF2BP2 ablated in macrophages/microglia, associated with elevated expression of inflammatory cytokines in the brain. These mutant mice had larger infarctions 4 days after stroke associated with fewer anti-inflammatory M2 microglia/macrophages recruited to the peri-infarct area, suggesting an impaired clearance of injured tissues. Since IRF2BP2 modulates interferon signalling, and interferon beta (IFNβ) has been reported to be anti-inflammatory and reduce ischemic brain injury, we asked whether loss of IRF2BP2 in macrophages/microglia would affect the response to IFNβ in our stroke model. IFNβ suppressed inflammatory cytokine production of macrophages and reduced infarct volumes at 4 days after photothrombosis in wild type mice. The anti-inflammatory effect of IFNβ was lost in IRF2BP2-deficient macrophages and IFNβ failed to protect mice lacking IRF2BP2 in macrophages/microglia from ischemic injury. In summary, IRF2BP2 expression in macrophages/microglia is important to limit inflammation and stroke injury, in part by mediating the beneficial effect of IFNβ.